Effect of Source/Drain Electrode Materials on the Electrical Performance and Stability of Amorphous Indium-Tin-Zinc-Oxide FETs - An, Seong Ui; Ahn, Dae-Hwan; Ju, Gijun; Chen, Simin; Ji, Yo Seop; Han, Jae-Hoon; Kim, Jaekyun; Kim, Younghyun (Institute of Electrical and Electronics Engineers, 2024)
The gate-bias stability of amorphous indium-tin-zinc-oxide (a-ITZO) field-effect transistors (FETs) is critical for their display and emerging memory applications. However, a-ITZO FETs suffer from insufficient gate-bias stability induced by oxygen vacancies in the channel layer. To address this issue, we examined the impact of source/drain (S/D) electrode materials (W, Mo, and Ni) on the oxygen vacancy formation and electrical characteristics in the a-ITZO FETs. Through X-ray photoelectron spectroscopy (XPS) analysis, we found that the Ni S/D electrode is effective in forming fewer oxygen vacancies in the a-ITZO channel, whereas W and Mo induce many oxygen vacancies. Our proposed model suggests that the Ni electrode absorbing less oxygen from the a-ITZO films compared to other electrodes leads to fewer oxygen vacancies in the a-ITZO channel. Notably, the a-ITZO FETs incorporating Ni S/D electrodes exhibit not only excellent electrical performance, including a high field-effect mobility of 27.6 cm(2)/Vs, a steep subthreshold swing (SS) of 71.8 mV/decade, and high on/off ratio of similar to 10(7), but also an outstanding gate-bias stability (Delta V-th = -0.04 V) under negative bias stress (NBS) testing. These findings underscore the potential of Ni S/D electrodes in advancing the development of high-performance, stable a-ITZO FETs for the next-generation semiconductor devices.